DPP4-inhibitor improves neuronal insulin receptor function, Brain mitochondrial function and cognitive function in rats with insulin resistance induced by high-fat diet consumption - Noppamas Pipatpiboon (2018)
High-fat diet (HFD) consumption has been demonstrated to cause peripheral and neuronal insulin resistance, and brain mitochondrial dysfunction in rats. Although the dipeptidyl peptidase-4 inhibitor, vildagliptin, is known to improve peripheral insulin sensitivity, its effects on neuronal insulin resistance and brain mitochondrial dysfunction caused by a HFD are unknown. We tested the hypothesis that vildagliptin prevents neuronal insulin resistance, brain mitochondrial dysfunction, learning and memory deficit caused by HFD. Male rats were divided into two groups to receive either a HFD or normal diet (ND) for 12 weeks, after which rats in each group were fed with either vildagliptin (3 mg/kg/day) or vehicle for 21 days. The cognitive function was tested by the Morris Water Maze prior to brain removal for studying neuronal insulin receptor (IR) and brain mitochondrial function. In HFD rats, neuronal insulin resistance and brain mitochondrial dysfunction were demonstrated, with impaired learning and memory. Vildagliptin prevented neuronal insulin resistance by restoring insulin-induced long-term depression and neuronal IR phosphorylation, IRS-1 phosphorylation and Akt/PKB-ser phosphorylation. It also improved brain mitochondrial dysfunction and cognitive function. Vildagliptin effectively restored neuronal IR function, increased glucagon-like-peptide 1 levels and prevented brain mitochondrial dysfunction, thus attenuating the impaired cognitive function caused by HFD. © 2012 Federation of European Neuroscience Societies and Blackwell Publishing Ltd.